Accounting for Global Dispersion of Current Accounts - Lee, Jaewoo (IMF Working Papers; Working Paper ;, 2009)
We undertake a quantitative analysis of the dispersion of current accounts in an open economy version of incomplete insurance model, incorporating important market frictions in trade and financial flows. Calibrated with conventional parameter values, the stochastic stationary equilibrium of the model with limited borrowing can account for about two-thirds of the global dispersion of current accounts. The easing of financial frictions can explain nearly all changes in the current account dispersion in the past four decades whereas the easing of trade frictions has almost no impact on the current account dispersion.